An Empirical Study on the Learning Outcomes of Vocational Students in A Smart Classroom - Ye , Liu; Lu , Zhu (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: Smart Classrooms, as a form of rich-media learning environments, were increasingly being implemented and utilized. This study aimed to investigate the impact of Smart Classrooms on learning outcomes by examining 133 first-year vocational students from a vocational college in Yunnan Province, China. The research focused on an applied writing course and compared Cognitive, Behavioral, and Affective learning outcomes between the SEEWO Smart Classroom and traditional classrooms. Materials and Methods: In this study, 133 current vocational students participated. The participants were divided into two groups: a control group and a treatment group. The control group was taught in a traditional classroom while the treatment group was taught in a Seewo Smart Classroom. After a 10-week applied writing course, the course was evaluated using the course evaluation scale that had been used in the college for many years. This evaluation explored cognitive learning outcomes, behavioral learning outcomes, and affective learning outcomes in terms of final grades, classroom behavioral performance, and student course scoring. Results: Students in Smart Classrooms showed significant improvement in final exam scores, enhancing Cognitive learning outcomes. Behavioral outcomes, including participation and attendance, also increased. Student feedback favored Smart Classrooms over traditional settings, with no significant impacts from gender, age, or admission methods observed. Conclusion: Smart Classrooms notably enhanced Cognitive and Behavioral learning outcomes, indicating improved student performance and engagement. Positive student feedback underscores their potential to enhance educational experiences and outcomes compared to traditional classrooms.